A Pragmatic Study of the Commissive speech Act of Promise in Four of Donald Trump’s Famous Speeches - رغدة نعيم خضير; مناهل سلمان عويد (Journal of College of Education, 2023)
Speaking is a way to communicate in order to express thoughts, feelings, and information. It is not only about the sound; it is also about the significance and intent of the sound. Speech acts classified as "commissives" bind the speaker to future action. One of the commissives is the speech act of promising, which binds the speaker to the promise until it is unintentionally triggered. In this study, the speech act of promising is examined in four of Donald Trump’s well-known speeches. following Searle (1969), this study is a descriptive qualitative one. The study tries to identify the promising techniques that Donald Trump used in his political speeches. Additionally, it looks for the most common promising technique employed in the chosen talks. In summary, the study found that the word "promise", whether it is a noun or a verb and the modal verb "will" are both used to make promises in the chosen speeches. Compared to other words Trump employs to make promises, the word "promise" is used less frequently. The modal verb "will" is frequently used to follow through on a promise, and this is the main technique used in all of Trump’s chosen speeches. This verb is used more frequently in these speeches than the word "promise." Additionally, Trump uses it as his go-to phrase when making a commitment.